2012
DOI: 10.1890/11-0502.1
|View full text |Cite
|
Sign up to set email alerts
|

Shocks to the system: community assembly of the oak savanna in a 40‐year fire frequency experiment

Abstract: Abstract. Fire is a major force driving the evolution of plants and the structure and function of ecosystems globally. It thus likely operates as an important environmental filter that selects for species that have evolved to tolerate and depend on fire. Across a 40-year experimental fire gradient from frequently burned open savanna to unburned dense woodland in Minnesota, USA, we examined the relationships among community assembly, evolutionary history, and functional trait composition. Close relatives had si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
143
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(147 citation statements)
references
References 99 publications
3
143
0
1
Order By: Relevance
“…Other studies report similar results (Cavender- Bares & Reich, 2012;Peterson & Reich, 2001). Other studies report similar results (Cavender- Bares & Reich, 2012;Peterson & Reich, 2001).…”
Section: Changes In Functional Identitysupporting
confidence: 61%
See 1 more Smart Citation
“…Other studies report similar results (Cavender- Bares & Reich, 2012;Peterson & Reich, 2001). Other studies report similar results (Cavender- Bares & Reich, 2012;Peterson & Reich, 2001).…”
Section: Changes In Functional Identitysupporting
confidence: 61%
“…FD also decreased under climate change in certain stream fish assemblages(Buisson, Grenouillet, Villéger, Canal & Laffaille, 2013). For example, both PaulaLoiola et al (2010) and Cavender-Bares and Reich (2012) found no clear directional effect of fire frequency on FD Laughlin, Moore and Fulé (2010). For example, both PaulaLoiola et al (2010) and Cavender-Bares and Reich (2012) found no clear directional effect of fire frequency on FD Laughlin, Moore and Fulé (2010).…”
mentioning
confidence: 99%
“…Such a long time period covered more successional phases, resulting in a better ability to detect species turnover. Combining long-term and demographic data in phylogenetic studies is therefore a critical step for developing a clear understanding of the processes driving community assembly (see also Cadotte et al 2012, Cavender-Bares andReich 2012).…”
Section: Notesmentioning
confidence: 99%
“…Lienin and Kleyer, 2011;Cavender-Bares and Reich, 2012), indicate the role of multiple processes and the signature of spatial scale on those processes. We found that environmental and forest use gradients operate hierarchically over subtropical premontane tree species influencing the distribution of demographic and morphological traits.…”
Section: Resultsmentioning
confidence: 99%